Estudo de avaliabilidade da pol?tica nacional de aten??o integral ?s pessoas com doen?a falciforme e outras hemoglobinopatias no estado da Bahia - Souza, Madlene de Oliveira (2020)
This study aims to assess the extent to which the Policy for Comprehensive Care for People with Sickle Cell Disease and Other Hemoglobinopathies (PNAIPDF) in the state of Bahia allows for future evaluations. Was developed, an evaluability study with a descriptive and exploratory design through document analysis and semi-structured interviews with stakeholders. In this way, the methodology is organized in two moments: the elaboration and agreement of the logical model with the interested parties and elaboration of the evaluation matrix. The logical model presented elements that interact to produce results, achieve the objective and context elements that influence PNAIPDF in a favorable and unfavorable way. The indicator matrix was composed of 27 quantitative and qualitative indicators that are distributed in three dimensions: access to health actions and services, management, teaching and research, with respective variables, calculation method, parameter and premise. Thus the PNAIPDF in the State of Bahia presents measurable conditions for future evaluations. It is worth mentioning that the two instruments, the logical model and the evaluation matrix can be used in the three spheres of government and may support the performance of health evaluation studies of this policy.The present study also made it possible to identify the elements of context that have a favorable and unfavorable influence on the implementation of the PNAIPDF.